Humane Autonomous Technology Re-thinking Experience with and in Intelligent Systems - Rousi, Rebekah; von Koskull, Catharina; Roto, Virpi (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
XIX, 349 p. 23 illus., 9 illus. in color.